Diferensiasi Tingkat Upacara Pawintenan Kepemangkuan Di Lombok - I Made Agus Yudhiarsana (Jurnal Penelitian Agama Hindu, 2021)
The pawintenan ceremony has levels based on the implementation of the Dewa Yadnya or Rsi Yadnya ceremony. The types of pawintenan are Pawintenan Sari, Pawintenan Gede, Pawintenan Mapedamel Ganapati, Pawintenan Mapedamel Dasa Guna, and Pawintenan Samskara Ekajati or Panca Rsi, while the public is still confused in determining the level of the pawintenan ceremony, especially the pawintenan kepemangkuan. This research focuses on studies related to the level of the ceremony and the process of implementing the pawintenan pemangku or pinandita ceremony in Lombok. This study aims to provide an understanding of the level of the pawintenan ceremony of pemangku for the public in Lombok. This study uses descriptive research with a qualitative approach with data collection techniques using observation, interviews and documentation. Pemangku or pinandita are people who have gone through the pawintenan ceremony until Adiksa Widhi, but have not gone through the procession at the site and amati aran or changed names. The levels of pawintenan are divided based on the profession of the pawintenan Sastra or Saraswati, the pewintenan Sari or Pemangku, the pawintenan Dalang, the pawintenan Tukang, and the pawintenan Mahawisesa. The pawintenan ceremony based on the results of research on the Pemangku or Pinandita temples which are included in the temple Mataram City shows that the Pinandita or Pemangku groups the levels of the Pawintenan Pemangku ceremony in Lombok, especially in the city of Mataram into the three levels of the pawintenan ceremony are pawintenan alit, pawintenan madya and pawintenan ageng or agung. This division is based on the duties and responsibilities of pemangku or Pinandita. Which includes pawintenan alit is Pawintenan Sari atau saraswati, Pawintenan Madya is Pawintenan Pemangku, and Pawintenan Agung is Pawintenan Jero Gede or Bhawati, as the highest stage of the Ekajati ceremony in Lombok.